2018
DOI: 10.1177/1464420718816731
|View full text |Cite
|
Sign up to set email alerts
|

A study of interlaminar properties for a unidirectional glass fiber reinforced epoxy composite

Abstract: In this work, a numerical-experimental study of the interlaminar zone for an unidirectional glass fiber reinforced epoxy composite is carried out in order to predict the load-displacement curves of a double cantilever beam test. First, an experimental mechanical characterization of the laminated composite was made through quasi-static in-plane tensile and bending tests and out-of-plane delamination tests (i.e. double cantilever beam tests or opening mode I). The main results have shown that the elastic module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…According to Krasna et al [17], the resistance of the blocks with 25% plastic is suitable for these masonry to be used in the elaboration of exterior and interior partition walls. As Pincheira et al [43] indicated, recycled PET can be used to manufacture concrete with superior mechanical properties. With the compression results obtained in the current study it can be defined that by introducing different percentages of PET plastic and a certain amount of nanoadditive the resistance exceeds that of traditional blocks.…”
Section: Resultsmentioning
confidence: 99%
“…According to Krasna et al [17], the resistance of the blocks with 25% plastic is suitable for these masonry to be used in the elaboration of exterior and interior partition walls. As Pincheira et al [43] indicated, recycled PET can be used to manufacture concrete with superior mechanical properties. With the compression results obtained in the current study it can be defined that by introducing different percentages of PET plastic and a certain amount of nanoadditive the resistance exceeds that of traditional blocks.…”
Section: Resultsmentioning
confidence: 99%
“…The optimization of Search Directions is addressed with metaheuristics and optimization algorithms, which have been applied widely in the mechanical context, such as the optimization of the design of a composite riser using an elitist real-coded genetic algorithm in order to reduce the structural weight (Wang et al 2014), and determinate the interface parameters to reduce the distance between numerical and experimental load-displacement curve of a reinforced glass fiber epoxy composite using genetic algorithms (Pincheira et al 2018). Another examples can be found in (Corriveau et al 2010;Saitou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although these techniques require very high resolution equipment to capture the CTOD or FPZ, which can cost a lot of money and be difficult to implement in specimens tested in a controlled environmental. Another option is to use inverse methods for minimising the residual between experimental and numerical curves [ 44 , 63 , 64 , 65 , 66 ]. However, despite their simplicity, they are very time-consuming because it is necessary several virtual tests to evaluate different values of each parameter of the softening function .…”
Section: Introductionmentioning
confidence: 99%